Students' Perceptions of the Effectiveness of the 5E Learning Cycle and Problem-Based Learning Based on TPACK in Writing Scientific Article - Khairun Nisa; Syahrul Ramadhan; Harris Effendi Thahar (AL-ISHLAH: Jurnal Pendidikan, 2023)
Writing scientific papers is unavoidable for the scientific community in higher education. As part of the scientific community, students must master the knowledge and skills of writing scientific papers. However, the reality on the ground has not shown the expected reality. Many students do not have sufficient knowledge and skills to write scientific papers. Not a few students still have shallow knowledge and skills in terms of writing scientific papers. This study examined students' perceptions of using the TPACK-based 5E-PBL learning cycle model to improve their ability to write scientific papers. The subjects of this study were 189 second-semester students who had taken Indonesian language courses at Asahan University from the Faculty of Economics and the Faculty of Teacher Training. The research method used was a descriptive research design with a quantitative approach. The research data was obtained by distributing surveys to all samples using the Google Forms platform, and interviews. Based on the results of the data analysis, there was a significant increase, around 51 students got very good scores, and 65 were in a good category. Thus, the effectiveness of the TPACK-based 5E-PBL learning cycle model in terms of educators (lecturers) shows a very high category (56%). While the average score showed the highest score 41% in the very high category viewed from the students’ sub-variable. In sum, students considered using the 5E-PBL learning cycle model based on TPACK for Indonesian language courses on scientific paper writing material positively impacted the learning process.